Aggregation‐Induced Emission: Dynamic Visualization of Stress/Strain Distribution and Fatigue Crack Propagation by an Organic Mechanoresponsive AIE Luminogen (Adv. Mater. 44/2018). Issue 44 (5th November 2018) - Qiu, Zijie; Zhao, Weijun; Cao, Mingkui; Wang, Yuqi; Lam, Jacky W. Y.; Zhang, Zhe; Chen, Xu; Tang, Ben Zhong
Abstract : Stress is critically important for the manufacturing industry. The visualization of stress/strain distributions and fatigue crack propagation on metal specimens with a pure organic fluorescent material is achieved by Zhe Zhang, Ben Zhong Tang, and co‐workers in article number1803924 . Such a method enjoys the merits of a simple setup and real‐time, full‐field, on‐site, and direct visualization. The invisible information of the mechanical response of the metal specimens are transformed to visible fluorescent signals.